Nitrogen-doped pyrite composite for enhanced Fe(III)/Fe(II) cycling and broad-spectrum pollutant degradation via peroxymonosulfate activation - Yan Yan; Zhenjie Li; Chunwei Liu; Yuan Qiao; Caiping Hu; Longquan Zhang; Xiaoguo Shi; Yizhe Zhao; Yawei Gu; Wenyu Wang (Process Safety and Environmental Protection, 2026)

A methodical comparative analysis of the improved dechlorination of trichloroethylene (TCE) using C-, N-, and S-modified zero-valent iron (ZVI) - Xiang Luo; Hongwei Chen; Hongjian Shen; Ling Zhang; Jinbo Chen; Shuai Liu; Bo Gao; Honglei Zhang; Yawei Gu (Journal of Water Process Engineering, 2026)

Enhanced simultaneous removal of TCE and Cr(VI) by nitrided nano zero-valent iron (FexN@nZVI): Performance and mechanisms - Ling Zhang; Guangfei Gao; Fengxu Shang; Xinze Song; Zhenjie Li; Lei Chen; Junjie Zhang; Wenyu Wang; Xiaoguo Shi; Bo Gao; Yawei Gu; Xuan Zhang (Journal of Environmental Chemical Engineering, 2026)

Activation of peroxydisulfate with N-doped CoFe2O4 for tetracycline hydrochloride degradation: the predominant role of radical and singlet oxygen cooperation - Jiawei Wei; Xia Chen; Yawei Gu; Wenqiang Jiang (Journal of Water Process Engineering, 2026)

Rapid cultivation regulation of Methyl tert-butyl ether degradation consortium: Effects of supplemental carbon source and mechanism - Wenhao Guo; Sunyin Wang; Jun Gu; Zixi Ming; Wei Wang; Xin Song; Yawei Qian; Manjun Zhan; Ran Yu (Journal of Environmental Chemical Engineering, 2025)

Radical and non-radical peroxymonosulfate activation induced by a novel ferromagnetic Fe1-xS/lignin-based biochar nanocomposite: Multi-pathway synergistic effects for bisphenol A removal - Minglu Zhang; Zunqing Wen; Longquan Zhang; Qingyun Wang; Lihua Zang; Qing Feng; Yawei Gu; Wenyu Wang; Ke Ma; Hao Zhang; Dandan Ji; Jun Liu; et al. (Chemical Engineering Journal, 2025)

A novel N/C co-modified FeS2 nanocomposite synthesized by wet-mechanochemical method for efficient peroxymonosulfate activation and nearly 100% SO4•─ selective generation - Longquan Zhang; Guangfei Gao; Xiaoguo Shi; Zunqing Wen; Minglu Zhang; Qingyun Wang; Qing Feng; Jing Sun; Xuezheng Liu; Ying Zhao; Yawei Gu; Wenqiang Jiang (Chemical Engineering Journal, 2025)

The Preconditioning with Sevoflurane Alleviates Hypoxia-Reoxygenation-Induced Myocardial Cell Injury by Regulating the lncRNA LINC00265/miR-370-3p Axis - Yangge Shao; Qiang Gu; Yawei Yuan; Long Wang; Taowei Yu (Cardiovascular Toxicology, 2025)

Co-incorporation of C and S into zero-valent iron to enhance trichloroethylene dechlorination: Kinetics, electron efficiency, and dechlorination capacity - Xuan Zhang; Siyu Xu; Yawei Gu; Ling Zhang; Longquan Zhang; Fengxu Shang; Xinze Song; Zhen Wang; Xiaoguo Shi; Honglei Zhang; Runze Bi; Jinbo Chen (Journal of Environmental Chemical Engineering, 2025)

Air oxidation behavior of wet-mechanochemically synthesized pyrite FeS2: Fenton performance regulated by Fe species, sulfur vacancy and crystal facet ratio - Zunqing Wen; Xiaoguo Shi; Huiying Sui; Minglu Zhang; Longquan Zhang; Yawei Gu; Qing Feng; Ke Ma; Na Zhang; Mingzhe Wang; Ruiyan Zhang; Chongqing Xu; et al. (Chemical Engineering Journal, 2025)

Hedge three-dimensional reconstruction and motion control technology for trimming robot - Jin Gu; Bin Zhang; Yu Wang; Yawei Zhang (Computers and Electronics in Agriculture, 2024)

Prevalence of antibiotic resistance genes, heavy metal, and bacterial community composition in sea sediments influenced by Eriocheir sinensis breeding aquaculture - Hui Fu; Wei Sun; Yawei Cao; Qing Li; Xiaotong Wang; Zijie Zhou; Qian Meng; Tingyi Luo; Wei Gu; Qingguo Meng (Environmental Science and Pollution Research, 2024)

Enhanced Fenton performance of wet-mechanochemically synthesized FeS2/Biochar: The multiple synergistic effect derived from mutual element doping - Zunqing Wen; Xiaoguo Shi; Yawei Gu; Ke Ma; Xiaozhe Song; Ao He; Chen Wang; Nianbo Zhang; Huiying Sui; Chongqing Xu; Rong Xue (Chemical Engineering Journal, 2024)

Linking the removal of enrofloxacin to the extracellular polymers of microalgae in water bodies: A case study focusing on the shifts in microbial communities - Youyin Hu; Shangsheng Sun; Xuewei Gu; Ziyi Li; Jialin Zhang; Yawei Xing; Liqing Wang; Wei Zhang (Environmental Science and Pollution Research, 2024)

Nanoplastics and chrysene pollution: Potential new triggers for nonalcoholic fatty liver disease and hepatitis, insights from juvenile Siniperca chuatsi - Tiantian Chen; Hewei Jiang; Yaoji He; Yawei Shen; Zequn Huang; Yifeng Gu; Qun Wei; Jinliang Zhao; Xiaowu Chen (Science of The Total Environment, 2024)

Proteome and gut microbiota analysis of Chinese mitten crab (Eriocheir sinensis) in response to Hepatospora eriocheir infection - Yawei Cao; Leiting Zhang; Yue Yang; Jiaying Li; Xiaoqi Luan; Xiaoli Xia; Wei Gu; Jie Du; Keran Bi; Li Wang; Qingguo Meng (Aquaculture, 2024)

Degradation of norfloxacin by sulfur-doped iron-cobalt oxides activated perodisulfate: Synergism between free radicals and singlet oxygen - Luwei Zhai; Fengchun Li; Yuhai He; Xia Chen; Xuan Zhang; Yawei Gu; Chongqing Xu; Guihuan Yan; Xiaojing Feng; Wenqiang Jiang (Chemical Engineering Journal, 2023)

Protective effect of chicken egg yolk immunoglobulin (IgY) against Spiroplasma eriocheiris infection in Chinese mitten crab - Ying Guo; Yubo Ma; Hendriansyah Endri; Yanlan Huang; Xinyu Pan; Suyue Qiu; Yawei Cao; Wei Gu; Jie Du; Li Wang; Qingguo Meng (Aquaculture, 2023)

Potential for selective oxidation of aniline in soil washing effluent by active chlorine and testing its practicality - Yi Ren; Xiangxin Meng; Xuan Zhang; Yuhai He; Guangfei Gao; Pengqi Wang; Yawei Gu; Yue Ding; Wenqiang Jiang (Chemosphere, 2023)

Early evidence of trepanation along the Yellow River Basin in Neolithic China - Yawei Zhou; Shuang Lin; Wanfa Gu; Letian He; Qun Zhang; Hui-Yuan Yeh (Archaeological and Anthropological Sciences, 2020)
Trepanation is a long-lasting ancient practice found around the world with diverse motivations. However, the distribution and motivation of intentional trepanation in China remain unclear. This study presents one of the earliest trepanations on a male adult individual who is unearthed from the Shuanghuaishu site in Gongyi, Henan, dating back to the late Yangshao cultural period (3500–2900 BC). The macroscopic and microscopic observation, alongside with micro-CT scan, are conducted to further evaluate the conditions on the edges of the perforation and intracranial situation. The oval perforation is located on the occipital bone, and neither fracture nor apparent healing signs are observed on the margins. Archeological evidences and simulated experiment indicate that the trepanation could be conducted by drilling the tables of the skull with a V-bladed stone tool. In view of the location of the perforation and the limited details on the edges, the motivation behind the trepanation could be due to the medical treatment of trauma on the occipital bone or a postmortem ritual. The analysis of the early trepanation along the Yellow River Basin provides further evidence on the ancient human behavior and enriches our understanding of the origin and distribution of trepanation in Neolithic China.

Expression profile analyses of mettl8 in Oryzias latipes - Wei Pang; Ziwei Zhao; Yawei Shen; Yanhui Bi; Yifeng Gu; Xiaowu Chen (Fish Physiology and Biochemistry, 2020)